Bisphenol A exerts estrogenic effects by modulating CDK1/2 and p38 MAP kinase activity. Issue 8 (3rd August 2014) - Lee, Hee-Seok; Park, Eun-Jung; Oh, Jae-Ho; Moon, Guiim; Hwang, Myung-Sil; Kim, Sang-Yub; Shin, Min-Ki; Koh, Young-Ho; Suh, Jin-Hyang; Kang, Hui-Seung; Jeon, Ju-Hong; Rhee, Gyu-Seek; et al.
Abstract: Bisphenol A (BPA) is considered to be an endocrine disruptor, but the mechanisms by which it disrupts endocrine functions are poorly understood. Here, we have shown that BPA binds both estrogen receptor (ER)-α and ER-beta (ER-β) using a fluorescence polarization competitive binding assay. In addition, we found that BPA induced cell proliferation by modulating cell cycle-related genes in the MCF-7 human mammary cancer cell line. Moreover, using a BG1 luciferase ER transactivation assay, we found that BPA has estrogenic activity. Modulating the MAPK pathway by using an ERK inhibitor (PD98059) or a JNK inhibitor (SP600125) had no effect on the ability of BPA to induce estrogenic activity. However, the antiestrogen, ICI 182, 780, and the p38 inhibitor, PD 169316 successfully blocked BPA-induced estrogenic activity. Our findings suggest that BPA mimics ER-dependent estrogenic activity by targeting proteins that regulate the cell cycle and p38 MAPK. Graphical abstract: : Bisphenol A exerts estrogen receptor–dependent estrogenic activity by targeting proteins that regulate the cell cycle and p38 MAPK.